A Novel Platelet Activating Factor Antagonist, SM-12502, Attenuates Endotoxin-induced Disseminated Intravascular Coagulation and Acute Pulmonary Vascular Injury by Inhibiting TNF Production in Rats - Murakami, Kazunori; Okajima, Kenji; Uchiba, Mitsuhiro; Johno, Masayoshi; Okabe, Hiroaki; Takatsuki, Kiyoshi (Thrombosis and Haemostasis, 1996)
Adult respiratory distress syndrome and disseminated intravascular coagulation are important pathologic conditions affecting the outcome of patients with sepsis. To elucidate the possible therapeutic efficacy of SM-12502, a novel platelet activating factor antagonist, on acute lung injury and disseminated intravascular coagulation in sepsis, we investigated the effect of SM-12502 on an endotoxin (ET)-induced septic model in rats. SM-12502 prevented ET-induced increases in pulmonary vascular permeability and ET-induced histologic changes, such as leukocyte infiltration and pulmonary interstitial edema, 6 h following the administration of ET (5 mg/kg). SM-12502 also inhibited the decrease in fibrinogen and the increase in fibrin and fibrinogen degradation products observed following ET administration. SM-12502 prevented increases in the serum concentration of tumor necrosis factor (TNF) 90 min following ET administration in vivo, and significantly inhibited the production of TNF-α by ET-stimulated monocytes in vitro.These findings suggest that SM-12502 attenuates the actions of endotoxin by the inhibition of TNF production